2020
DOI: 10.1016/j.jns.2020.116980
|View full text |Cite
|
Sign up to set email alerts
|

Multiple internal border zone infarcts in a patient with COVID-19 and CADASIL

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the commonest inherited stroke disorder. We report a novel presentation of multiple internal border zone infarcts in a patient with COVID-19 and CADASIL. The clinical significance of this case is to highlight the risk of COVID-19 exacerbating CADASIL. Possible pathophysiological mechanisms are discussed, which may be extrapolated to patients with cerebral small vessel disease and non-CADASIL strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…To date there are several reports on neurological complications of COVID-19. We divided the neurological symptoms in such patients into three different groups: symptoms related to CNS involvement [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101]...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date there are several reports on neurological complications of COVID-19. We divided the neurological symptoms in such patients into three different groups: symptoms related to CNS involvement [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101]...…”
Section: Resultsmentioning
confidence: 99%
“… Cerebrovascular events 3 Ischemic Stroke 37 Articles [ 39 ], [ 57 ], [ 58 ], [ 60 ], [ 63 ], [ 73 ], [ 74 ], [ 75 ], [ 76 ] [ 77 ], [ 78 ], [ 79 ], [ 80 ],. [ 81 ], [ 82 ], [ 83 ], [ 84 ], [ 85 ], [ 86 ], [ 87 ], [ 88 ], [ 89 ], [ 90 ], [ 91 ], [ 92 ], [ 93 ], [ 94 ], [ 95 ], [ 96 ], [ 97 ], [ 98 ], [ 99 ], [ 100 ], [ 101 ], [ 102 ], [ 178 ], [ 192 ] 363 NR in all articles. In large population studies ischemic stroke was reported in 1% [ 77 ] to 2.5% [ 84 ] of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both thrombotic microangiopathy related to direct or indirect damage by SARS-CoV-2 on the endothelium of cerebral small vessels and brain-blood-barrier injury related to hypoxemia have been hypothesized. An emblematic case of the possible causality of the association between COVID-19 and IS in a patient with CADASIL is reported ( 95 ). The few described cases of IS caused by spontaneous carotid dissection also fall into the TOAST etiopathogenetic category of “other determined etiology,” which collects data on the known rare causes of IS.…”
Section: Discussionmentioning
confidence: 99%
“…In those with pre-existing intracranial stenosis, for example, hypoxemia could lead to infarction due to a mismatch between oxygen supply and demand (52). Similarly, cerebral hypoperfusion secondary to the downregulation of the RAS could increase the risk of both large vessel and SVD infarction, with a typical border-zone distribution (53,54).…”
Section: Page 13 Of 24mentioning
confidence: 99%